Enzymatic Study in Sera of Chronic Renal Failure Patients Undergoing Hemodialysis - Azzam Abdulsattar Mosa (College of Education for Pure Sciences, 1999)
Abstract This study involved an estimation of the activity of some enzymes such as xanthine oxidase (X.O), acidic and alkaline deoxyribonuclease (DNase), peroxidase and pepsinogen in sera of patients with chronic renal failure (CRF) which treated with hemodialysis. Blood samples of 32 patients with chronic renal failure from both sexes were compared with (63) samples taken from healthy individuals as a control group. The results showed a significant increase in the activity of xanthine oxidase, acidic and alkaline DNase and pepsinogen enzyme i Enzymatic Study in Sera of Chronic Renal Failure Patients Undergoing Hemodialysis n serum of patients with CRF before and after hemodialysis compared with control for both sexes. A significant decrease was noted in activity of peroxidase in sera of patients with CRF before and after hemodialysis compared to control group for both sexes. The results also demonstrated that the hemodialysis process caused a significant reduction (P<0.001) in the activity of xanthinoxidase and pepsinogen. No significant effect (P<0.05) for hemodialysis on the reduction of acid DNase and elevation of alkaline DNase levels was noted. Hemodialysis had a significant increase (P<0.001) on peroxidae activity. Furthermore, correlation coefficient between the levels of enzymes in sera of patients before and after hemodialysis were determined.